A Review of Gamification Impact on Student Behavioural and Learning Outcomes - Nurtanto, Muhammad; Kholifah, Nur; Ahdhianto, Erif; Samsudin, Achmad; Isnantyo, Fajar Danur (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Gamification has become a new trend in learning in the 21st century, by utilizing technology with game elements to change behavior and support learning outcomes. However, few researchers have focused on the comprehensive impact of gamification in helping researchers to better understand developments over the past few years. The ScienceDirect, Taylor and Francis, Springer, Wiley, and SAGE publisher databases were surveyed and a total of forty articles from 2016-2021, were selected for review. Data analysis using NVivo 12 Plush software, with Hierarchy Chart and Mind Map methods. The main findings indicate the positive impact of gamification on student behavior and learning outcomes, including affective, cognitive, behavioral, and performance or others. The researcher recommends the continuity of gamification on learning outcomes and behavior, that interface design and teacher cognitive abilities are strategies or successful learning.